Adherence to guideline-directed medical therapy and its association with re-hospitalization and mortality following coronary artery bypass graft surgery. (25th November 2020) - Dankner, R; Orenstein, L; Laufer, K; Olmer, L; Ziv, A; Novikov, I; Moshkovitz, Y
Abstract: Objectives: We investigated associations with re-hospitalization, and intermediate- and long-term mortality, of cardio-thoracic surgeons' adherence to pharmacological guideline-directed medical therapy (GDMT) in discharge recommendations of coronary artery bypass graft (CABG) surgery patients. Methods: In this longitudinal multicenter study, 1, 131 patients who underwent elective CABG surgery in seven medical centers during 2004–2007 were interviewed in the hospital before surgery. Adherence of cardio-thoracic surgeons to GDMT was considered as prescribing medications from three families: antiplatelet therapy, beta-blockers and statins; and was determined from discharge letters. Patients were interviewed one-year after hospitalization to obtain information on re-hospitalizations and current medications. Mortality information was extracted from the Ministry of Internal Affairs registry and updated until March 2018. Results: GDMT adherence was evident in the discharge recommendations of 638 patients (56.4%). A propensity score (PS)-weighted multivariate logistic regression showed a 26% lower 1-year risk of re-hospitalization/mortality among patients whose discharge recommendations reflected full adherence than among patients whose recommendations reflected partial adherence (OR=0.74, 95% CI: 0.57–0.97, p=0.03). A PS-weighted Cox proportional hazard model showed 24% lower intermediate (8 year)-term mortality hazard among patients with cardio-thoracic surgeons' adherence to GDMT, compared to other patients (HR=0.76, 95% CI: 0.59–0.98, p=0.03); however the protective effect was attenuated when examining long (14 year)-term mortality. Short- and intermediate-term protective effects were also found when considering only adherence to beta-blockers or statins. Use of GDMT increased 1-year after CABG surgery only in patients who attended cardiac rehabilitation programs after surgery and not in those who did not attend cardiac rehabilitation during that year. Conclusions: The reference in CABG patients' discharge recommendations to GDMT was associated with a lower 1-y re-admissions/mortality and lower intermediate-term mortality. Cardio-thoracic surgeons should adhere closely to preventive medication guidelines. Cardiac rehabilitation is associated with better post CABG surgery patients preventive treatment. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Israel National Institute for Health Policy